The learning experiences of mentees and mentors in a nursing school’s mentoring programme - Annemarie Joubert; Johanna de Villiers (Curationis, 2015)
Background: A School of Nursing supports third-year undergraduate students (mentees) by means of a mentoring programme in which critical-care nursing students (mentors) are involved. However, the programme designers needed to find out what gaps were evident in the programme.